Comparison of tuberculosis indicators after implementation of the clinical protocol for tuberculosis and HIV management in Iranian prisons: a quasi-experimental study. Issue 6 (28th April 2020) - SeyedAlinaghi, SeyedAhmad; Farhoudi, Behnam; Ataeinia, Bahar; Dadras, Omid; Hosseini, Mostafa; Jafari, Sirous; Mazaheri-Tehrani, Elham; Alasvand, Ramin; Shahbazi, Mohammad; Mohraz, Minoo
Abstract : Purpose: The aim of this study was to compare the defined indicators of tuberculosis (TB) control program in the intervention and control prisons, after implementation of the national clinical protocol for TB and HIV management in Iranian prisons, suggesting active health service provision in all steps of service provision. Design/methodology/approach: This was quasi-experimental study conducted among inmates of two prisons in Iran. Great Tehran prison was purposively chosen as the intervention prison and Karaj prison was purposively chosen as control prison as well. Intervention and control prisons were compared in terms of the TB indicators within three periods (before intervention, during implementation and follow-up period) from October 2013 to June 2014. Findings: Number of inmates with TB symptoms who underwent TB workup was four times more in intervention prison compared to control prison (9.3 vs 2.5 cases out of 1, 000 inmates per month in the case prison compared to the control prison). Such difference was also significant in the intervention prison, comparing before and during the intervention period. The patient finding in case prison increased significantly after the intervention (223.6 vs 81.8 cases out of 100, 000 inmates per year). The number of TB cases who received HIV testing increased from 50 to 100%. Originality/value: Active health service provision has significantly improved indicators in the intervention prison. The authors recommend implementation of this guideline in all prisons of Iran. Integration of other diseases with high burden among prisoners is also recommended in the active health services provision.